2021
DOI: 10.51201/jusst12648
|View full text |Cite
|
Sign up to set email alerts
|

Study of Alcoholic Extract of Acacia Farnesiana (L.) Willd Pods

Abstract: Identification of bioactive compound from alcoholic extract of Acacia farnesiana leguminosae pods by using preliminary phytochemical test or thin layer chromatography and the quantification of total phenolic content by folin-ciocalteu reagent method. shade dried grounded powder of Acacia farnesiana pods was successively extracted with petroleum ether, chloroform and alcohol in soxhlet apparatus, alcoholic compound obtained in more amount as compare to other two extract so alcoholic extract was used for identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Kadam and McMillan investigated the feasibility of bio-EtOH production with corn stover as a renewable feedstock in 2002 and pointed out about 80 million tons of dry corn stover could be available for bioethanol production. 88 Several reports have studied the production of bioethanol with only corn stover or with a mixed corn/corn stover system since then, with variations in several factors including pre-treatment method, corn stover varieties and solid loading. 61,88,90,93 Wheat straw and rice straw are another family of food crops residues and studies have shown the feasibility of producing bio-EtOH with these agricultural wastes.…”
Section: Ethylenementioning
confidence: 99%
See 2 more Smart Citations
“…Kadam and McMillan investigated the feasibility of bio-EtOH production with corn stover as a renewable feedstock in 2002 and pointed out about 80 million tons of dry corn stover could be available for bioethanol production. 88 Several reports have studied the production of bioethanol with only corn stover or with a mixed corn/corn stover system since then, with variations in several factors including pre-treatment method, corn stover varieties and solid loading. 61,88,90,93 Wheat straw and rice straw are another family of food crops residues and studies have shown the feasibility of producing bio-EtOH with these agricultural wastes.…”
Section: Ethylenementioning
confidence: 99%
“…88 Several reports have studied the production of bioethanol with only corn stover or with a mixed corn/corn stover system since then, with variations in several factors including pre-treatment method, corn stover varieties and solid loading. 61,88,90,93 Wheat straw and rice straw are another family of food crops residues and studies have shown the feasibility of producing bio-EtOH with these agricultural wastes. 100,101 Belal has reported the utilization of rotted rice straw residues for bio-EtOH production with optimization of pH and temperature for the microorganism mediated saccharification process.…”
Section: Ethylenementioning
confidence: 99%
See 1 more Smart Citation